Application of Exponential Smoothing Method in Forecasting the Number of Visitors to Kinantan Zoo Bukittinggi, Indonesia - Alya Nasyifa Putri; Muhammad Adzan (Journal of Applied Mathematics and Modelling, 2025)
Kinantan Zoo Bukittinggi is one of the main tourist attractions in West Sumatra, experiencing fluctuations in visitor numbers due to various factors such as holidays, weather, and regional policies. Accurate visitor forecasting is essential for effective management, resource optimization, and strategic planning. This study aims to apply the Exponential Smoothing method to predict the number of visitors to Kinantan Zoo Bukittinggi. The forecasting model was evaluated using the Mean Absolute Percentage Error (MAPE) to assess its accuracy. Secondary data from the Bukittinggi City Tourism, Youth, and Sports Office covering the years 2012 to 2023 were analyzed. Microsoft Excel, with the Data Analysis and Solver tools, was used to process the data and optimize the smoothing parameter . The initial forecasting results yielded a MAPE value of 21%, indicating a reasonable level of accuracy. Further optimization using Solver reduced the MAPE value to 17%, demonstrating improved prediction reliability. The forecasted number of visitors for 2024 is approximately 937,665. The findings suggest that the Exponential Smoothing method is effective in predicting visitor trends at Kinantan Zoo. These results can assist in planning and decision-making, particularly in enhancing operational efficiency and marketing strategies. Future research may explore alternative forecasting models to further refine prediction accuracy.